Strategi Pemasaran Warung Coto Makassar Dalam Meningkatkan Pendapatan (Studi Kasus Di Kelurahan Poboya Kecematan Mantikulore Palu) - Nuraisyah Nuraisyah; Gita Farista; Syarif Permana Salingkat; Moh Wahyudin; Rofika Ramadani; Tasya Namira Budjuhari; Rasti Rasti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This research aims to find out how the marketing strategy is applied to increase the income of the coto cafe in Makassar. This research uses a qualitative research method that is conducted directly down to the space or location. The data collection technique used in this research is interviews, using interview guidelines that have been systematically and comprehensively compiled for data collection. The results of the research show that the marketing strategy carried out by Makassar coto stalls in increasing revenue is to always provide coto with more content and maintain the taste, always looking at the quality of the meat purchased and for the service provided by Mr. Leman so that customers feel comfortable, which is to always maintain the cleanliness of the place effort, the quality of products such as buying meat should not be mixed with fat. Warung coto Makassar owned by Mr. Leman has not cooperated with digital platforms such as courier services because the requirements are quite difficult.